Stres: Faktor pemicu bunuh diri pada orang dewasa dan cara pencegahannya - Latifa, Dina Tiara (Maliki Interdisciplinary Journal, 2024)
This article discusses the triggering factors of suicide in adults caused by stress. The research explores the relationship between stress and the risk of suicide in adults, as well as prevention strategies that can be used to reduce the impact of stress and prevent suicidal behavior. Through a literature study method, the author presents information on signs of stress that may lead to suicidal behavior, effect of mental health as well as effective interventions to reduce stress and support the mental health of adults. The article also provides practical guidance for individuals and healthcare professionals to address stress and prevent suicide in adults.